Multi-environment Performance Evaluation and Stability Analysis of Large Seeded Faba Bean (Vicia faba) Genotypes in High Potential Areas - Yimam, Kedir; Yilma, Gizachew; Achenef, Gebeyaw (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during the main cropping seasons of 2016, 2017 and 2018 at Kulumsa, Bekoji, Asasa and Kofele in potential areas of South Eastern Ethiopia from June to November with the objective to assess the performance of faba bean genotypes for grain yield and yield stability. Twelve faba bean genotypes were evaluated using randomized complete block design with four replications under rain-fed condition. The combined analysis of variance revealed that grain yield of faba bean was significantly influenced by genotype (15.8%), environment (32.6%) and genotype by environment interaction (51.6%). The highest mean grain yield was obtained from G-12 (3692.3 kg ha-1) and G-10 (3619.0 kg ha-1) with an overall mean yield of 3403.9 kg ha-1 across nine environments while the lowest yield recorded from G-8. The first two principal components of AMMI biplot showed that PC 1 explained 47.8% and PC 2 accounted 19.6% of the genotype by environment interaction sum of squares. Some genotypes, such as G-12, G-10, G-1, G-7 and G-5 exhibited significantly higher yields than the average, while others had yields lower than the average. Genotypes G-10, G-6 and G-2 showed the highest stability consistently based on most stability parameters, AMMI and GGE biplot analysis. G-10 could be considered as ideal genotype due to its high yield and stability which was widely adaptable across environments. Finally, top ranked genotypes G-10, G-7 and G-5 were identified for both grain yield and seed weight.